The equation above holds true for positive integers and . Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Starting with I = 2 ∫ 0 2 π l n ( s i n 2 x ) d x
Substitute 2x=t , reduce the integral & replace t with x and it is now : ∫ 0 π l n ( s i n x ) d x
Using ∫ 0 2 a f ( x ) d x = 2 ∫ 0 a f ( x ) d x if f(2a-x)=f(x) we get 2 1 I = ∫ 0 2 π l n ( s i n x ) d x
2 1 I = ∫ 0 2 π l n ( s i n x ) d x = ∫ 0 2 π l n ( c o s x ) d x
I = ∫ 0 2 π ( l n ( s i n x ) + l n ( c o s x ) ) d x ⟹ I = ∫ 0 2 π l n ( 2 s i n 2 x ) d x = ∫ 0 2 π ( l n ( s i n 2 x ) − l n 2 ) d x
I = ∫ 0 2 π l n ( s i n 2 x ) d x − ( 2 π l n 2 )
The braced integral is nothing but 2 1 I as we started with
I = 2 1 I − π l n 2 ⟹ I = − π l n 2
⟹ A = 1 , B = 2 ⟹ A + B = 3